Effect of On-Demand Oral Pre-exposure Prophylaxis With Tenofovir/Emtricitabine on Herpes Simplex Virus-1/2 Incidence Among Men Who Have Sex With Men: A Substudy of the ANRS IPERGAY Trial. (8th November 2018) - Chaix, Marie-Laure; Charreau, Isabelle; Pintado, Claire; Delaugerre, Constance; Mahjoub, Nadia; Cotte, Laurent; Capitant, Catherine; Raffi, François; Cua, Eric; Pialoux, Gilles; Tremblay, Cécile; Meyer, Laurence; et al.
Abstract: We evaluated the impact of on-demand oral tenofovir disoproxil fumarate (TDF)/emtricitabine (FTC) for pre-exposure prophylaxis (PrEP) on herpes simplex virus (HSV)-1/2 incidence among men who have sex with men (MSM) enrolled in the ANRS IPERGAY trial. Serum samples were tested at baseline and at the last visit for HSV-1/2 antibodies. Overall HSV-1 incidence was 11.7 per 100 person-years; 16.2 and 7.8 per 100 person-years in the TDF/FTC and placebo arm, respectively ( P = .19). Overall HSV-2 incidence was 7.6 per 100 person-years; 8.1 and 7.0 per 100 person-years in the TDF/FTC and placebo arm, respectively ( P = .75). On-demand oral PrEP with TDF/FTC failed to reduce HSV-1/2 incidence in this population.